2021
DOI: 10.6060/mhc210130z
|View full text |Cite
|
Sign up to set email alerts
|

Photoinactivation of S. Aureus by Сationic meso-Arylporphyrin and Its Zn(II) Complex

Abstract: In this work, cationic meso-arylsubstituted porphyrin and its Zn(II) complex were synthesized. The compounds were characterized by multinuclear NMR spectroscopy, electronic spectroscopy and ESI-mass spectrometry. The photodynamic activity of the porphyrins was studied in relation to S. aureus bacteria and their biofilms. Application of polymeric micelles of Pluronic F-127 as nanosized delivery vehicles supports high antimicrobial photodynamic activity of the synthesized porphyrins. The influence of the central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…For instance, rose bengal and chlorin e6 (20 μM) inactivated only 0.6 and 1.2 log 10 of S. aureus with high light doses of 30 and 20 J/cm 2 , respectively. It is worth noting that the light dose needed to effectively kill S. aureus (>3.0 log 10 ) with CPVBP2 (1.2 J/cm 2 ) is also significantly lower than many reported photosensitizers, including traditional photosensitizers, such as porphyrin, phthalocyanine, phenothiazinium, boron-dipyrromethene, indocyanine green, and AIE photosensitizers. , …”
Section: Resultsmentioning
confidence: 93%
“…For instance, rose bengal and chlorin e6 (20 μM) inactivated only 0.6 and 1.2 log 10 of S. aureus with high light doses of 30 and 20 J/cm 2 , respectively. It is worth noting that the light dose needed to effectively kill S. aureus (>3.0 log 10 ) with CPVBP2 (1.2 J/cm 2 ) is also significantly lower than many reported photosensitizers, including traditional photosensitizers, such as porphyrin, phthalocyanine, phenothiazinium, boron-dipyrromethene, indocyanine green, and AIE photosensitizers. , …”
Section: Resultsmentioning
confidence: 93%
“…In our studies [134][135][136][137], we investigated the antimicrobial activity against S. aureus and E. coli bacteria and their biofilms for cationic meso-arylporphyrins with A4 and AB-AB structure with terminal pyridinium groups (Figure 15). In these works, we modified the following parameters in the structure of the compounds: (1) the hydrophilichydrophobic balance varied depending on the number of methylene spacers (2, 4, 5, 10); In our studies [134][135][136][137], we investigated the antimicrobial activity against S. aureus and E. coli bacteria and their biofilms for cationic meso-arylporphyrins with A4 and ABAB structure with terminal pyridinium groups (Figure 15). In these works, we modified the following parameters in the structure of the compounds: We have shown that the efficiency of the used РS decreases with the increasing length of the methylene spacers, which is associated with an increase in their hydrophobicity, and hence with the aggregation processes in aqueous media.…”
Section: Other Cationic Derivativesmentioning
confidence: 99%
“…In the study of photoinduced effect of PS on S. aureus bacterial biofilms, 100% inhibition of viable bacteria was recorded for compounds 29-30a,b at concentrations of 10 µM. The maximal degree of inhibition (82%) was achieved for zinc complex 30b against E. coli biofilms [134,135]. The mechanism of photodynamic action against bacterial biofilms of Gram-positive S. aureus strain was investigated by confocal laser microscopy [134].…”
Section: Other Cationic Derivativesmentioning
confidence: 99%